Evaluasi Diri Perilaku Profesional di Institutsi Sekolah Tinggi Ilmu Kesehatan Guna Bangsa Yogyakarta - Widuri Widuri; Amitya Kumara; Tridjoko Hadianto (Journal of Health (JoH), 2014)
Background: Education world has a very important role in improving the quality of human resources, as it is the environment in which the process of the formation of professional behavior through a series of teaching and learning process. Professional behavior should be clearly seen as an aspect of personal identity and character developed over time. Based on this, the focus of professionalism began to shift from individual to the institution and stated that professionalism must be embedded in an educational institution with a complete integration of the culture of professionalism that involves the institution leader, staffs, lecturers, and students. The purpose of this study is to investigate the professional behavior of the institution of Sekolah Tinggi Ilmu Kesehatan Guna Bangsa Yogyakarta. Methods: This study is a descriptive qualitative research. Subjects were the institutional leader, lecturers, staffs and students are determined by purposive sampling. Interview instruments include altruism, honor and integrity, caring and compassion, respect for others, responsibility and accountability, excellence and scholarship, and leadership. Participant at the data collection focused group discussion (FGD) is 10 persons and on interview data collection is 21 persons. Efforts to achieve the credibility of the informant are done by triangulation and discussions with colleagues. Research supervisor role as auditors, maintain dependency and certainty degree of this research. Results: Participants considered that the lecturers, staffs, students and institutional leader have done with the guidance of a good, high integrity, good communication, mutual respect, responsibility and provide exemplary. However, some behavioral components still require improvement such as the level of lecturers’ discipline, staffs’ job and responsibility distribution, student discipline and responsibility, and supervisor leadership patterns. Conclusion: As there are still some components of professional behavior that needs any improvement, requires institutions to increase self-understanding and awareness to professional behavior. Institutions need to consider any strategies to be taken to overcome any problems faced by the institution to achieve professional behavior.